Adaptation of the organizational culture profile scale into Indonesian: A psychometric study - Utomo Triyo; Handoyo Seger; Fajrianthi (BIO Web of Conferences)
The Organizational Culture Profile (OCP) is widely utilized to assess organizational culture. However, there has been no documented scientific study on its adaptation to the Indonesian language in reputable international journals. This study aims to adapt the OCP scale to Indonesian and evaluate its psychometric properties. A quantitative methodology was employed, involving 453 participants from government organizations in East Java, Indonesia. Confirmatory Factor Analysis (CFA) utilizing a five-factor model demonstrated that the measurement model met various fit indices, indicating a strong alignment between the model and field data. Additionally, the analysis confirmed the OCP scale's convergent validity. These findings affirm that the Indonesian version of the OCP scale is a valid research instrument.